Tyrophagus perniciosus Zakhvatkin 1941 - Cilbircioğlu, Cihan; Çobanoğlu, Sultan (Zenodo, 2019)
Tyrophagus perniciosus Zakhvatkin, 1941 Width: 308.83 ± 7.13 (225.91–387.34), length: 505.07 ± 8.84 (388.14–616.39) (n = 10). Specimens examined Hanönü / Donalar Village, 16.IV.2015 (3 ♀♀, 2 ♂♂); Taşköprü/ Aşağıçayırcık Village, 20.IV.2015 (5 ♀♀, 9 ♂♂); Taşköprü/ Yukarıçayırcık Village, 20.IV.2015 (5 ♀♀, 6 ♂♂); Taşköprü/ Kızılcaören Village, 25.IV.2015 (11 ♀♀, 14 ♂♂); Centrum / Çavundur Village, 01.V.2016 (3 ♀♀, 8 ♂♂). Comments This mite is in the mold mites group (Zhang and Fan 2005). They are mostly found in stored bodies, organic fertilizers, greenhouses, plant residues and dead arthropods living in soil. This species is an economically important mite for the stored agricultural products (Zhang and Fan 2005). It was found in the head, green parts and storage surveys and determined intensely in land surveys.

Published as part of Cilbircioğlu, Cihan & Çobanoğlu, Sultan, 2019, Phytophagous mite (Acari) species on garlic (Allium sativum L.) cultivation areas and storages of Kastamonu, Turkey, pp. 211-224 in Persian Journal of Acarology 8 (3) on pages 217-218, DOI: 10.22073/pja.v8i3.46349, http://zenodo.org/record/7173998

{"references": ["Zhang, Z. - Q. & Fan, Q. - H. (2005) Revision of Tyrophagus Oudemans (Acari: Acaridae) of New Zeland and Australia. Landcare Research Contract Report, LC 0405 / 149, New Zealand Ltd., Auckland, New Zealand, 291 pp."]}
Keywords: Arthropoda; Arachnida; Tyrophagus perniciosus; Animalia; Biodiversity; Sarcoptiformes; Tyrophagus; Taxonomy; Acaridae